Environmental education as a key factor of environmental consciousness - ISAKOVA, Nataliia; DANKEVYCH, Liudmyla (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
Understanding the phenomenon of environmental education and implementation of its principles in the cultural life of our contemporary is an urgent problem of today. The integrity of the natural environment for human existence, and the acquisition of skills necessary for an individual in the contemporary society depend on the level of environmental upbringing and environmental education of people, and the younger generation, in particular. Environmental education aims to help people understand the causes of environmental changes and to propose the ways to prevent them. The article highlights the aims, subject matter & peculiarities of environmental education, its influence on the formation of environmental consciousness of the younger generation in Ukraine. Environmental knowledge is regarded as a prerequisite for the development of environmental consciousness, and their successful acquisition forms environmental outlook.